Dual Angular Tunability of 2D Ge/ZnSe Notch Filters: Analysis, Experiments, Physics. Issue 5 (20th December 2022) - Ko, Yeong Hwan; Lee, Kyu Jin; Simlan, Fairooz Abdullah; Gupta, Neelam; Magnusson, Robert
Abstract: 2D resonant gratings enable dual angular tunability by controlling the plane of incidence (POI) under linear polarization. If the POI is set to be perpendicular to the electric field vector (s‐polarization or transverse electric (TE) polarization), an excited TE mode provides spectral tuning. The orthogonally propagating transverse magnetic (TM) mode is robust in angle. Conversely, if the POI is set for p‐polarization, an excited TM mode provides the tuning. Detailed explanations of the underlying physical processes are set forth by decomposing the 2D lattice into equivalent 1D gratings using second‐order effective‐medium theory. This is shown to work extremely well even for a strongly modulated lattice with refractive‐index contrast of 3. With proper design and corresponding experiments, a widely tunable notch filter covering long‐wave infrared bands is demonstrated. Experimentally varying the incidence angle up to 16° under p‐polarization, a notch channel in TM mode tunes across a band exceeding 0.5 µm with the TE channel remaining at a constant wavelength. The interesting appearance of a resonance channel originating in diagonally propagating leaky modes is briefly examined. The analysis and experiments presented can be useful for realizing diverse 2D tunable filters while furnishing methodology for detailed understanding of the attendant near fields and mode structure. Abstract : Resonant metamaterials based on 2D optical lattices enable dual angular tunability by controlling the plane of incidence under linear polarization. The comprehensive analysis and experiments presented can be useful for design and fabrication of diverse, compact, low‐loss tunable filters while furnishing methodology for detailed understanding of the attendant near fields and mode structure.